Participatory identification of climate-smart agriculture priorities - Simelton, Elisabeth; Duong, Minth Tuan; Le VH (2016)
With the concept climate-smart agriculture (CSA) being relatively new, there is a need to test and develop practical and systematic methodologies and approaches for documenting and evaluating CSA practices in the field. The implementation of CCAFS’ Climate-Smart Villages (CSV) involves identifying, assessing and selecting climate-smart farming practices.